Digital-Based Educational Information Management in Enhancing Student Interest: Scrutinizing the Mediating Role of Madrasah - Uuh Buchori; Encep Syarifudin; Eko Wahyu Wibowo; Enung Nugraha (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
Digital transformation has increasingly reshaped how Islamic educational institutions manage information, communicate institutional value, and attract prospective students. However, limited empirical evidence explains whether institutional image still mediates the relationship between digital-based educational information management and student interest, particularly in Islamic secondary education. This study examines the direct effect of Digital-Based Educational Information Management (DBEIM) on Student Interest and tests the mediating role of Madrasah Image among State Islamic Senior High Schools in Banten Province, Indonesia. A quantitative explanatory survey design was employed, involving 535 student respondents selected through proportional stratified random sampling. Data were collected using a structured questionnaire and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The measurement model confirmed adequate reliability and validity, with indicator loadings ranging from 0.720 to 0.915, Cronbach’s Alpha values between 0.935 and 0.961, Composite Reliability values between 0.949 and 0.973, and AVE values between 0.715 and 0.818. The structural model showed that DBEIM had a strong positive effect on Student Interest (β = 0.711, t = 18.245, p = 0.000) and significantly improved Madrasah Image (β = 0.654, t = 14.321, p = 0.000). However, Madrasah Image did not significantly affect Student Interest (β = -0.040, t = 0.632, p = 0.528) and did not mediate the DBEIM–Student Interest relationship (β = -0.022, t = 0.624, p = 0.533). These findings challenge the assumption that institutional image consistently functions as a mediating mechanism and suggest that, among digital-oriented madrasah students, interest is shaped more directly by digital utility, information accessibility, and service responsiveness than by general institutional image